STEM occupations are different – just like women : why general concepts to increase women's interest in STEM occupations are not sufficient - Schad-Dankwart, Inga [Verfasser]; Krämer, Heike [Verfasser]; Conein, Stephanie [Verfasser] (My University, 2021)
"The question of how to increase the proportion of women in STEM occupations has been discussed for many years. Frequently, however, no distinction is drawn between individual STEM occupations. Closer examination reveals differences. Whereas some of the occupations actually do display a very low proportion of women, female representation in other STEM occupations is even above 50 percent. What makes some of these occupations attractive to women? And why are other occupations still rarely chosen despite having similar contents? These questions were investigated as part of the BIBB project “Women choose STEM”." (authors' abstract; BIBB-Doku)
Keywords: S 6.3.1 Ingenieurberufe, Chemiker, Physiker, Mathematiker; P 1.3 Frauen; 370; MINT-Berufe; Produktionsberuf; Werkstattberuf; Geschlechterverteilung; Frauen; Berufsentscheidung